2021
DOI: 10.3389/fpsyt.2021.679437
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Brain Abnormalities in Internet Gaming Disorder and Attention-Deficit/Hyperactivity Disorder: A Comparative Meta-Analysis

Abstract: Background: Patients with Internet gaming disorder (IGD) and attention-deficit/hyperactivity disorder (ADHD) have high comorbidity but it is still unknown whether these disorders have shared and distinctive neuroimage alterations.Objective: The aim of this meta-analysis was to identify shared and disorder-specific structural, functional, and multimodal abnormalities between IGD and ADHD.Methods: A systematic literature search was conducted for whole-brain voxel-based morphometry (VBM) and functional magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 137 publications
4
23
0
Order By: Relevance
“…A comparative meta-analysis of whole-brain voxel-based morphometry (VBM) studies found disorder-specific grey-matter volume (GMV) abnormalities in the putamen in patients with IGD and in the orbitofrontal cortex in those with ADHD, while both conditions shared a lower GMV in the prefrontal cortex [ 37 ]. Functional magnetic resonance-imaging (fMRI) research comparing IGD versus ADHD found that ADHD was associated with a disorder-specific hypoactivation of the left median cingulate cortex (MCC), middle temporal gyrus (MTG), right caudate nucleus, and left middle frontal gyrus [ 37 ]. Alternatively, individuals with IGD were characterized by the activation of the bilateral precuneus/cingulate cortex (CC), right OFC, MTG, left precentral gyrus, bilateral IFG, and right caudate nucleus [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative meta-analysis of whole-brain voxel-based morphometry (VBM) studies found disorder-specific grey-matter volume (GMV) abnormalities in the putamen in patients with IGD and in the orbitofrontal cortex in those with ADHD, while both conditions shared a lower GMV in the prefrontal cortex [ 37 ]. Functional magnetic resonance-imaging (fMRI) research comparing IGD versus ADHD found that ADHD was associated with a disorder-specific hypoactivation of the left median cingulate cortex (MCC), middle temporal gyrus (MTG), right caudate nucleus, and left middle frontal gyrus [ 37 ]. Alternatively, individuals with IGD were characterized by the activation of the bilateral precuneus/cingulate cortex (CC), right OFC, MTG, left precentral gyrus, bilateral IFG, and right caudate nucleus [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Functional magnetic resonance-imaging (fMRI) research comparing IGD versus ADHD found that ADHD was associated with a disorder-specific hypoactivation of the left median cingulate cortex (MCC), middle temporal gyrus (MTG), right caudate nucleus, and left middle frontal gyrus [ 37 ]. Alternatively, individuals with IGD were characterized by the activation of the bilateral precuneus/cingulate cortex (CC), right OFC, MTG, left precentral gyrus, bilateral IFG, and right caudate nucleus [ 37 ]. Therefore, the structural and functional alterations in both ADHD and IGD subjects were in the PFC areas, and, more specifically, in those associated with reward, such as the anterior cingulate cortex (ACC).…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in the structure of putamen have been reported in patients with IGD. Functional magnetic resonance imaging analysis has also demonstrated increased activation in the bilateral cingulate cortex, anterior insula, and striatum [ 8 ]. Impaired cognitive control in patients with IGD leading to compulsive gaming behavior may be related to increased striatum volume.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrollable, excessive, and compulsive use of internet games has become an important social problem, which is known as internet gaming disorder (IGD) ( 5 ). Abundant research has demonstrated that IGD has a significant influence on physiological and psychological health ( 6 8 ). Due to these serious consequences of IGD, the World Health Organization (WHO) considered it as a clinical disease in the latest version of the International Classification of Diseases ( 9 ).…”
Section: Introductionmentioning
confidence: 99%